APPLICATION OF DETERMINATION OF CULINARY BUSINESS OPPORTUNITIES STUDY WITH THE SAW METHOD AS A TOURIST ATTRACTION IN THE DIGITAL ERA - Hartatik Hartatik (Yayasan Education and Social Center, 2022)
In the development of technology, more and more people are using the products of technology development to facilitate their daily activities. However, to determine opportunities when opening a culinary business, people usually choose according to their own estimates without using a system that is able to help the community to determine a business opportunity, including people in XYZ District, Central Java Province. In this situation, a Decision Support System (DSS) can be developed, which is a computer-assisted decision-making process to assist decision-makers by using certain data and models to solve some unstructured problems. The calculation method used is Simple Additive Weighting (SAW) with the basic concept of finding the weighted sum of the performance ratings on each alternative on a criterion. The features that can be used are storing master data such as alternative data, criteria data, and attribute data and generating a list of recommendations for the type of culinary business and the categorie of the culinary business in XYZ District. This system is expected as a means to help the community when making decisions to choose a culinary business at XYZ District in Central java as a tourism attaction in digital era